RETRACTED: COVID-19 Vaccine Hesitancy and Resistance in India Explored through a Population-Based Longitudinal Survey - Srikanth Umakanthan; Sonal Patil; Naveen Subramaniam; Ria Sharma (Vaccines)
Background: The World Health Organization has recommended that individual governments identify vaccine hesitancy areas. It is proposed that the governments, with the aid of local organizations, educate and implement social insights on the vaccination so that high population levels are covered with this safe immune program. Methods: A longitudinal online survey covered 3000 adults from India. We examined the demography, behavioral (socio-economic) attitude, vaccine hesitancy, vaccine resistance for the COVID-19 vaccine. The specific reasons for the COVID-19 vaccine decline were also evaluated. Results: Our survey revealed 59% definite response, 29% low-level response, and 7% high-level response for vaccine hesitancy, while 6% had resistant views on the COVID-19 vaccine. Individuals who had higher income levels, lived in a society, maintained social distancing, had downloaded the COVID-19 update app, showed a positive attitude towards their government, and more confidence in their healthcare system were more inclined towards the vaccination. On the contrary, individuals who had overstated the risks of COVID-19 and had a religious and populistic attitude towards vaccination were more hesitant/resistant to vaccination. The respondents who declined vaccine administration were further evaluated for their specific reason for their response. The most common reasons for declining the COVID-19 vaccine were post-vaccine scare of adverse health effects and accepting the information spread by social media. Conclusions: The results in our study show that by identifying population “hot spots” that have negative or unclear information on the COVID-19 vaccination, these “hot spots” can be addressed by involving friendly organizations that can clear their strong disbeliefs and increase the percentage of vaccine-definite people within the population. The role of government-induced COVID-19 vaccine policy measures can always be beneficial to cause this shift from disbelief to confidence within the population.